Cinéma médiéval : trois niveaux de sens d’une expression ambiguë - Corneliu Dragomirescu (Itinéraires)
By focusing upon the choices of the filmmakers and the process of creation that demands the invention of facts (even “historical” ones), the article explores three ways of interpreting “medieval cinema”. 1. Films actually set in the historical Middle Ages, either for aesthetic and dramatic reasons, or following ideological or economic motivations. 2. The form of cinema appearing in a story set in the Middle Ages, with an audience looking upon projected images (visions of the past, parallel actions). 3. When medieval aesthetics penetrate the language of film (visual, narrative), indifferent of the period depicted.